2004
DOI: 10.1590/s0034-72992004000500003
|View full text |Cite
|
Sign up to set email alerts
|

Proposta de modelo de atendimento multidisciplinar para disfonias relacionadas ao trabalho: estudo preliminar

Abstract: A disfonia tem recebido um enfoque ocupacional crescente e torna-se necessário, ao otorrinolaringologista, atualizar a abordagem clínica dos trabalhadores que usam a voz como instrumento de trabalho, onde novas catagorias profissionais têm surgido e, com elas, as disfunções vocais conseqüentes às condições de trabalho. Hoje, há grandes preocupações com o prejuízo econômico e produtivo que o ditúrbio vocal possa gerar. Sabe-se que a disfunção vocal tem como característica a multicausalidade e, por isso, a avali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
22

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 16 publications
1
31
0
22
Order By: Relevance
“…Moreover, associations between teachers' self-reported symptoms and causes were found, as outlined in Table 5. Researchers found that teachers were more likely to refer to vocal problems as age increases, the same way they found that teachers who did not have voice disorders are younger than those with voice changes 11,22 .…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Moreover, associations between teachers' self-reported symptoms and causes were found, as outlined in Table 5. Researchers found that teachers were more likely to refer to vocal problems as age increases, the same way they found that teachers who did not have voice disorders are younger than those with voice changes 11,22 .…”
Section: Resultsmentioning
confidence: 79%
“…The authors of that study also said that more women in the pedagogical area are due to the fact that the profession is still seen as traditionally feminine 22 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Female call center agents reported a higher degree of talkativeness at work when compared to men (Table 1). According to the literature, the females have a higher a risk factor for developing voice disorders than males, given that the laryngeal proportion of this gender and the vocal folds vibration dosage associated with vocal load can lead to a laryngeal hyperfunction and consequently development of lesions (21)(22)(23)(24) . When degree of talkativeness and vocal loudness are compared in the two situations studied, innate and at work, it is observed a greater degree of talkativeness and vocal loudness at work (Table 2).…”
Section: Discussionmentioning
confidence: 99%